2019
DOI: 10.1016/j.jcot.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Cadaveric study of the infrapatellar branch of the saphenous nerve: Can damage be prevented in total knee arthroplasty?

Abstract: Background: The infrapatellar branch of the saphenous nerve (IPBSN) is a purely sensory nerve innervating the anteromedial aspect of the knee and anteroinferior knee joint capsule. Total knee arthroplasty (TKA) is commonly used to treat end-stage arthritis, but the IPBSN is often injured and results in numbness around the anteromedial knee. The aim of this cadaveric study was to describe the course and variability of the IPBSN and to assess whether it is possible to preserve during a standard midline surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
(44 reference statements)
1
18
0
Order By: Relevance
“…This finding is supported by Lee et al. [ 4 ]. In this cadaveric study, infrapatellar branches of saphenous nerve were identified proximally to the tibial tubercle leading the authors to conclude that that there was no consistent way to preserve lateral skin innervation using a traditional midline approach.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This finding is supported by Lee et al. [ 4 ]. In this cadaveric study, infrapatellar branches of saphenous nerve were identified proximally to the tibial tubercle leading the authors to conclude that that there was no consistent way to preserve lateral skin innervation using a traditional midline approach.…”
Section: Discussionsupporting
confidence: 85%
“…Numbness surrounding the incision after total knee arthroplasty is a frequently reported outcome with rates ranging from 27% to 100% [ [1] , [2] , [3] ]. Denervation is caused by damage to the medial femoral cutaneous nerve and infrapatellar branch of the saphenous nerve which course from medial to lateral and provide sensation to the lateral skin [ 4 ]. Both nerves are disrupted during routine total knee arthroplasty by traditional midline incisions [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However a study performed by Kerver et al found that the location of the IBSN is highly variable, and a safe zone is therefore difficult to define before incision [22]. A recent cadaveric study by Lee et al claimed that there was no consistent way to preserve the IBSN using a standard midline approach in TKA and patient education on this complication is therefore important [23].…”
Section: Discussionmentioning
confidence: 99%
“…The MPFQ-complex is a crucial soft tissue element that needs to be repaired. It contains in addition a medial patellotibial ligament and a medial patellomeniscal ligament [9][10][11][12].…”
Section: New Surgical Techniquementioning
confidence: 99%